Study of nutrition in poor children in Lima - Aguilar, Telésforo (1954)
It has made the study of nutrition in 102 school children from poor class of Lima, aged 6 to 14 years, with the following results: From the clinical point of view it has been found in a high percentage of vitamin deficiency B complex, to a lesser extent anemic and other signs of undernutrition witness statements, due to poor nutrition, according to the survey practiced states. Almost 50% have been observed decreased size and weight compared with normal subjects of the same age. The biochemical analysis of the blood revealed a decrease in total protein and its fractions in almost all cases; in 67% hemoglobin levels were below normal. There is a marked percentage of children with accelerated sedimentation rate, unrelated to active pulmonary processes. We observed a marked hipoascorbinemia in almost all, according to the very poor intake of vitamin C from their food. Determinations of inorganic phosphorus and alkaline phosphatase in serum are presented in another paper by Dr. A. Guzman Barron. In summary, we believe, according to the above data, which exists in children, especially biochemical states of undernutrition poor sort of Lima signs, due to poor nutrition, in part correctable with proper educational guidance.